Analisis Wacana Kritis Teks Berita Konser Dan Acara Besar Boleh Kembali Digelar Pada Portal Berita Kompas - Cecio Oviela Aginta; Abdurrahman Yahya; Devi Aulya Wibowo; Yohanes Arie Kuncoro (Communicology: Jurnal Ilmu Komunikasi, 2022)
Mass media is a tool to convey information in the era of globalization. Mass media can also means as of delivering the results of journalistic activities. The results of this journalistic activities can be written in print or electronic form. Besides being easy to access, electronic mass media or online media is one of the easiest types of mass media to obtain and can be easily spread widely. One of these online media is Kompas.com. This research is using a qualitative research method with the critical analysis discourse method of Teun A. Van Dijk. This study focuses on analyzing four news discourses on the Kompas.com news portal with the theme of the return of allowing concerts and big events. In this analysis, there are several structures analyzed, such as: macro structure, superstructure, semantic microstructure, syntactic microstructure, stylistic microstructure and rhetorical microstructure. From this research, there are guidelines and studies that must be obeyed to and carried out before holding concerts and large events. In addition, concerts and major events cannot be held evenly in all regions, due to differences in the rules and levels of PPKM in each region. Although the Minister of Communications and Informatics, Johnny G. Plate, suggested that there should be concerts and big events so that residents can live on with their activities as usual. The government is still expected not to rush into allowing concerts and large events to be held. This is because the government must remain alert in order to avoid transmission and a spike in the high number of Covid-19 cases.